Vasoactive Properties of a Cocoa Shell Extract: Mechanism of Action and Effect on Endothelial Dysfunction in Aged Rats - Pilar Rodríguez-Rodríguez; Kendal Ragusky; Sophida Phuthong; Santiago Ruvira; David Ramiro-Cortijo; Silvia Cañas; Miguel Rebollo-Hernanz; María Dolores Morales; Ángel L. López de Pablo; María A. Martín-Cabrejas; Silvia M. Arribas (MDPI AG, 2022)
Cocoa has cardiovascular beneficial effects related to its content of antioxidant phytochemicals. Cocoa manufacturing produces large amounts of waste, but some by-products may be used as ingredients with health-promoting potential. We aimed to investigate the vasoactive actions of an extract from cocoa shell (CSE), a by-product containing theobromine (TH), caffeine (CAF) and protocatechuic acid (PCA) as major phytochemicals. In carotid and iliac arteries from 5-month and 15-month-old rats, we investigated CSE vasoactive properties, mechanism of action, and the capacity of CSE, TH, CAF and PCA to improve age-induced endothelial dysfunction. Vascular function was evaluated using isometric tension recording and superoxide anion production by dihydroethidium (DHE) staining and confocal microscopy. CSE caused endothelium-dependent vasorelaxation, blocked by L-NAME, but not indomethacin, regardless of sex, age, or vessel type. CSE maximal responses and EC50 were significantly lower compared to acetylcholine (ACh). Arterial preincubation with CSE, TH, CAF or PCA, significantly reduced the number of vascular DHE-positive cells. Compared to adult males, iliac arteries from aged males exhibited reduced ACh concentration-dependent vasodilatation but larger CSE responses. In iliac arteries from aged male and female rats, preincubation with 10−4 M CSE and PCA, but not TH or CAF, improved ACh-relaxations. In conclusion, CSE has vasodilatory properties associated with increased nitric oxide bioavailability, related to its antioxidant phytochemicals, being particularly relevant PCA. Therefore, CSE is a potential food ingredient for diseases related to endothelial dysfunction.